Struktur Populasi dan Morfometrik Kerbau Lumpur Pada Pola Pemeliharaan Traditional - Kurniawan, Isal; Yendraliza; Rodiallah , Muhamad; Definiati, Neli (Fakultas Pertanian dan Peternakan Universitas Muhammadiyah Bengkulu, 2024)
The buffalo farming system in Pangean District, Kuantan Singingi Regency is still This study aims to examine the characteristics of buffalo farmers, population structure and size of buffaloes whose husbandry system is based on local wisdom. This research was conducted from June to September 2022 in the location of smallholder farms in Pangean sub-district, Kuansing Regency. The selected villages were Pauh Angit Hulu, Pulau Tengah, and Tanah Bekali. The sample used was 30 buffalo farmers who are members of hereditary buffalo farmers with colony pens. The total number of buffaloes measured was 300. Data on population structure was taken from the Livestock Service Office. Parameters measured were; farmer profile, husbandry aspects, population structure and buffalo body size. Data were analysed descriptively by displaying mean, percentage and standard deviation. The results of this study are the profile of buffalo breeders consisting of the gender of breeders dominated by men with the highest education of junior high school. The application of technical aspects includes 48.9% breeding, 46.6% cage aspect, 40% feed aspect, 59.96% health aspect. Local wisdom of farmers is found in the aspect of cages on customary land, and the use of traditional medicines. Male buffalo body length is 135 cm and female body length is 124 cm. Buffalo population structure is 1 male; 15 females. Keywords: Aspects of maintenance, local wisdom, morphometrics, buffalo